Investigating Positive and Negative Affects in Collaborative Information Seeking: A Pilot Study Report - Gonzalez-Ibanez, R (2012)
Emotions and other affective processes have long been considered a key component in people s life. Despite research conducted in several research domains, little is known about the role of emotions in the information seeking process of both individuals and teams. This poster presents preliminary results from a pilot study conducted in order to evaluate design decisions, experimental protocol, tasks, and the system that will be used in research aiming to investigate the implications of positive and negative affects in the information search process of both individuals and teams. The pilot study involved 12 subjects randomly assigned to five experimental conditions in which a common information search task was performed. In each session, facial expressions, eye tracking data, electrodermal activity, desktop activity, users actions, and searches as well as communication logs were collected. In addition, as sessions were conducted, observations about subjects behaviors, system problems, and research protocols were made. Results from this pilot study suggests effects of both positive and negative affects at the level of performance, communication, and perceived difficulty, among other aspects. In addition to these preliminary findings, the poster also contributes a unique methodology, involving a rigorous design, for conducting such user studies.
Keywords: Affects; Collaborative search; Interactive search